Deep eutectic solvents in liquid-liquid extraction : correlation and molecular dynamics simulation /: correlation and molecular dynamics simulation. (2022) - Naik, Papu Kumar; (Researcher in chemical engineering), Kumar, Nikhil; Paul, Nabendu; Banerjee, Tamal
No abstract available